Fragility of safe asset markets - Thomas M. Eisenbach; Gregory Phelan (Federal Reserve Bank of New York, 2022)
We model a safe asset market with investors valuing safety, investors valuing liquidity, and constrained dealers. While safety investors and liquidity investors can interact symbiotically with offsetting trades in times of stress, we show that liquidity investors' strategic interaction harbors the potential for selffulfilling fragility. Surprisingly, standard flight to safety in times of stress can have a destabilizing effect and trigger a dash for cash by liquidity investors. This explains how safe asset markets can experience price crashes, as in March 2020. The announcement and execution of policy interventions play important roles for the functioning of safe asset markets.
Keywords: C7; G01; G1; E4; E5; 330; safe assets; liquidity shocks; global games; Treasury securities; COVID-19